2018
DOI: 10.1002/ptr.6083
|View full text |Cite
|
Sign up to set email alerts
|

Thai herbal antipyretic 22 formula (APF22) inhibits UVA‐mediated melanogenesis through activation of Nrf2‐regulated antioxidant defense

Abstract: Thai herbal antipyretic 22 formula (APF22), a polyherbal formula, has been traditionally used to treat dermatologic problems including hyperpigmentation. Exposure of the skin to ultraviolet A (UVA) causes abnormal melanin production induced by photooxidative stress. This study thus aimed to investigate the protective effects of APF22 extracts and phenolic compounds, ferulic acid (FA), and gallic acid (GA; used as positive control and reference compounds), on melanogenesis through modulation of nuclear factor E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…The HRF extracts and HSP also enhanced a substantial Nrf2 activation in mouse skin, together with the upregulation of antioxidant defense enzymes GST and NQO-1. We and other studies have reported that activation of Nrf2 is involved in the mechanisms underlying the photoprotective effect of phytochemicals and botanical extracts against UVR-induced damage of the skin cells including melanocytes and keratinocytes (Chaiprasongsuk et al, 2016;Chaiprasongsuk et al, 2017;Onkoksoong et al, 2018). Our findings strongly suggested that the photoprotective actions of HRF extracts and HSP at concentrations of 30 μg/ml and 10 μg/ml, protected against UVA-induced photoaging of NHDFs.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The HRF extracts and HSP also enhanced a substantial Nrf2 activation in mouse skin, together with the upregulation of antioxidant defense enzymes GST and NQO-1. We and other studies have reported that activation of Nrf2 is involved in the mechanisms underlying the photoprotective effect of phytochemicals and botanical extracts against UVR-induced damage of the skin cells including melanocytes and keratinocytes (Chaiprasongsuk et al, 2016;Chaiprasongsuk et al, 2017;Onkoksoong et al, 2018). Our findings strongly suggested that the photoprotective actions of HRF extracts and HSP at concentrations of 30 μg/ml and 10 μg/ml, protected against UVA-induced photoaging of NHDFs.…”
Section: Discussionsupporting
confidence: 72%
“…generated during UVA exposure of the skin causes upregulation of MMPs, in particular MMP-1, responsible for the degradation of the ECM proteins including collagen that contributes to photoaging (Pittayapruek et al, 2016). We previously reported that the Thai Herbal HRF extracts protected against UVA-induced MMP-1 in keratinocyte HaCaT cells (Pluemsamran et al, 2013) and melanogenesis in B16F10 melanoma cells through activating Nrf2-dependent antioxidant defenses (Onkoksoong et al, 2018). In this study, we determined the anti-photoaging effects of HRF extract and its possible active ingredient, hesperetin (HSP), on normal human dermal fibroblasts in vitro and on mouse skin in vivo exposed to UVA in association with modulation of Nrf2-related antioxidant signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound suppressed these cells both in vitro as well as in xenografts in mice. -Using an herbal antipyrelic formula UVA-A mediated melanogenesis was inhibited through the activation of Nrf2 regulated antioxidant defenses (Onkoksoong et al, 2018). -A recent broad-based mechanistic study of inhibitors of cytosolic thioredoxin reductase 1 in many tumor types produced impaired growth of syngeneic mouse tumors and viability of human tumors xenografts with little mitochondrial toxicity (Stafford et al, 2018).…”
Section: New Anti-melanoma Therapeutic Approaches Based On Redox-relamentioning
confidence: 99%
“…Regulation of MITF starts from signal transduction after α-MSH bind to MC1R receptor which stimulates mitogen-activated protein kinase (MARKs) which is serine/threonine kinase and also include extracellular signaling-regulated kinase (ERK) and also p38 as well. Several studies found that melanin synthesis is controlled by several signaling pathways such as phosphotidylineasital-3-kinase (PI3K/AKT) can be suppressed by natural substances which contain polyphenol group through ERK signaling pathway of B16F10 mouse melanoma cells 5,6.…”
Section: Introductionmentioning
confidence: 99%